STRUCTURAL SHIFTS IN THE NEO-INDUSTRIAL MODEL OF HUMAN CAPITAL DEVELOPMENT - Vladimir V. Guzyr; Sergey V. Potyagaylov; Anastasia V. Zhavoronok; Ekaterina S. Vorobyova (Векторы благополучия: экономика и социум, 2021)
The relevance of the research topic is caused by the problems of development of socially significant key sectors of the national economy. The gap formed during attempts to modernize existing relationships leads to a natural imbalance between the requirements and the possibilities of implementation within the framework of socio-economic processes. These processes stimulate the development of negative structural changes within the existing model of market relations. The lack of adjustments to the consequences of a negative structural shift, at best, will lead to stagnant processes in the economy, and at worst – to obsolescence of the material and technical base, followed by the requirement to restore/replace the missing elements of functioning in a particular technological order. The emerging problem field puts the need for goal-setting in the direction of creating an integrated approach to solving two interrelated problems within the framework of the theory of new industrialization: overcoming negative structural shifts in the development of new industrialization (6th technological order) with parallel reproduction/development/use of modern human capital and stimulation its involvement in innovative modernization of the industrial complex. A person as an economic unit can act as an element that neutralizes negative structural changes due to his involvement, both from the point of view of the producer and from the point of view of the consumer of goods and services of the new economic formation. As a result of the study, the key tools for reproduction and involvement of human capital in existing innovation processes have been formulated.